Hero on the Western Front discovering Alvin York's Great War battlefield - Kelly, Michael 1947- (Frontline Books, 2018)
"They knew it was the end. Weakened by four years of war, the reality had finally dawned on the Germans that their armies could never stop the combined might of the Allied forces, now bolstered by the fresh, enthusiastic Americans, who were now determined to be involved in the conflict that had engulfed the world.The US effort in 1918, in what became known as the Hundred Days Offensive, was focused on the Argonne Forest. It was there that 1,200,000 men were deployed in what was to be the largest offensive in the United States' military history.It was in the fighting in the Argonne Forest that one of the most remarkable incidents in the entire First World War took place. In October 1918, Corporal Alvin Cullum York single-handedly captured 132 Germans and killed twenty-one in a desperate fire-fight.York's battalion of the 328th Infantry Regiment had become pinned down by heavy machine-gun and artillery fire.
Keywords: York, Alvin Cullum -- 1887-1964; Westfront; Soldat; Erster Weltkrieg; USA; York, Alvin; World War, 1914-1918 / Personal narratives